2015
DOI: 10.1074/jbc.m114.596551
|View full text |Cite
|
Sign up to set email alerts
|

A Novel MEK-ERK-AMPK Signaling Axis Controls Chemokine Receptor CCR7-dependent Survival in Human Mature Dendritic Cells

Abstract: Background: Chemokine receptor CCR7 promotes survival in mature dendritic cells (mDCs). Results: Activated AMP-dependent kinase (AMPK) induces apoptosis in mDCs; CCR7 uses the kinases MEK1/2-ERK1/2 to regulate phosphorylation of AMPK on Ser-485 and consequently its inhibition. Conclusion: CCR7 uses a novel MEK1/2-ERK1/2-AMPK signaling axis to induce survival in mDCs. Significance: AMPK is a potential target to regulate mDC-mediated immune responses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
40
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 58 publications
3
40
0
Order By: Relevance
“…In murine macrophage-like RAW 264.7 cells, Park et al (12) showed that IKK␤ phosphorylates AMPK at Ser 485 in response to LPS treatment in mature dendritic cells. ERK1/2 was recently shown to phosphorylate AMPK on this serine residue (13), an effect that may be an important part of the mechanism by which CCR7 signaling promotes cell survival. Furthermore, protein kinase A (PKA) has been reported to act as an upstream kinase for AMPK Ser 485/491 in INS-1 cells in response to forskolin or GIP stimulation (14) and in human diploid fibroblasts in response to lysophosphatidic acid (15).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In murine macrophage-like RAW 264.7 cells, Park et al (12) showed that IKK␤ phosphorylates AMPK at Ser 485 in response to LPS treatment in mature dendritic cells. ERK1/2 was recently shown to phosphorylate AMPK on this serine residue (13), an effect that may be an important part of the mechanism by which CCR7 signaling promotes cell survival. Furthermore, protein kinase A (PKA) has been reported to act as an upstream kinase for AMPK Ser 485/491 in INS-1 cells in response to forskolin or GIP stimulation (14) and in human diploid fibroblasts in response to lysophosphatidic acid (15).…”
Section: Discussionmentioning
confidence: 99%
“…Also, in the hypothalamus, Dagon et al (4,5) showed that p70S6K phosphorylates AMPK␣2 Ser 491 to inhibit AMPK activity and decrease food intake. Others have shown that in murine macrophage-like RAW 264.7 cells, IKK␤ phosphorylates AMPK at Ser 485 in response to LPS treatment (12), while ERK1/2 can inhibit AMPK by this mechanism in mature dendritic cells in response to CCR7 signaling (13). Finally, protein kinase A (PKA) has been reported to phosphorylate this site in INS-1 cells in response to forskolin or GIP stimulation (14) and in human diploid fibroblasts in response to lysophosphatidic acid (15).…”
mentioning
confidence: 99%
“…Recombinant PKA (cAMP-dependent protein kinase) also phosphorylates AMPKα1 Ser487 in vitro , and cAMP-elevating agents have also been reported to stimulate AMPKα1 Ser487 phosphorylation in mouse embryonic fibroblasts and insulin-secreting cell lines [19,20]. Recently, inhibitors of the mitogen-activated protein kinase kinase (MEK1/2) extracellular signal-regulated kinase 1/2 (ERK1/2) and IKK (inhibitor of nuclear factor-κB kinase) pathways have also been reported to attenuate AMPKα1 Ser487 phosphorylation in human dendritic cells and a mouse macrophage cell line, implicating these pathways as regulators of AMPKα1 Ser487 [21,22]. …”
Section: Introductionmentioning
confidence: 99%
“…Polymet’s ability to activate the AMPKα pathway while simultaneously inhibiting mTOR suggests its mechanism of synergy with CDDP. The AMPK pathway is known to intersect with the congogenic Ras/Phosphatidylinositol 3-kinase (PI3K)/mTOR and extra cellular signal regulated kinase (ERK) pathways at multiple points [38,39]. Collectively, it is known that AMPK responds to a decrease in cellular ATP by phosphorylating effectors that inhibit mTOR activity.…”
Section: Resultsmentioning
confidence: 99%